Documenting trauma : an analysis of the construction of traumatic collective memory in the first and last scenes of the documentary, Mama Marikana - Saragas, Aliki (Centre for Film and Media Studies, 2015)
On 16 August 2012, the South African Police Service opened fire on rock-drill operators who had gone on a wildcat strike demanding a living wage of R12500, at the Lonmin Platinum mine in Marikana. Thirty-four mineworkers were left dead, seventy-eight were wounded and over two hundred and fifty were arrested. The shooting on 16 August was dubbed the ‘Marikana Massacre’, and has been compared to the lethal use of force during the Sharpeville massacre in 1960 (South African History Online, “Marikana Massacre 16 August 2012”). The documentary by Rehad Desai, Miners Shot Down has made a valuable contribution to balancing media representation of the events and the mineworkers’ perspectives, but to date the media has neglected to adequately engage with the plight of the widows and other women left behind in Marikana after the massacre. In reaction to the neglect and marginalisation that they experienced the women of the community formed the Marikana Women’s Organisation, Sikhala Sonke, in Wonderkop near Marikana. ! My film, Mama Marikana, aims to give a voice to the women of Marikana: the widows, mothers, sisters and community members left behind and forgotten by society after the Marikana massacre. It takes a look behind the miners’ story as five Marikana women struggle to move from a space of oppression to a space of empowerment. The film exposes a personal account of how women fight within a traumatised space: through the growth of the women’s organisation, Sikhala Sonke, one member’s rise to Parliament, personal sacrifices for the community and the empowerment of victims. The cinema of memory culminates at the intersection of history, documentary and cinema (Rabinowitz 120). By combining film with memory, and their multidimensional dreamlike “aura of insubstantiality” (MacDougal 29), documentaries can be involved in collective memory transmission in order to break officially imposed silences and contribute to different interpretations of history (Waterson 51). This study analyses how the montage editing of certain conventions of documentary filmmaking present in the first and last scene of my masters documentary Mama Marikana, transform it into a cinema of memory that allows for the transmission of a social, collective memory that can endure over time (Waterson 51). Previous work has failed to present how a structural analysis of montage editing and juxtaposition of conventions associated with the documentary form can transform a documentary into a cinema of memory. This research and my ! 5! documentary, Mama Marikana, attempt to create an alternative discourse on the role of memory creation within the traumatised and gendered space of Marikana. Using the concept of “cinema as language” (Carrol 1) and a qualitative structural analysis approach, the montage editing in the first and last scenes of Mama Marikana will be evaluated. Documentary conventions that will be considered include testimony (interviews with the widows and women of Sikhala Sonke Women’s Organisation), reenactment (a play in which the women act out their memories and interpretations of the massacre that took place on 16 August 2012), cinéma vérité footage [of the audience (male mineworkers) watching the women perform the play at the Marikana Commemoration Rally 2014] and archive footage (of the massacre that took place on 16 August 2012 and its aftermath). The research and film, Mama Marikana aim to provide a space where the women’s stories can be told and their voices heard. This includes the potential to make the personal political and to break official silences of traumatised spaces through the transmission of individual testimony into a social collective memory, where the film itself becomes an event/ memory performing its own meanings (Waterson 65). The combination of these documentary conventions allow the telling of an untold story that engages with subaltern voices in a liminal space trapped in traumatic history.